Development of Asymmetric Facial Depigmentation in a Patient Treated with Dasatinib with New-Onset Hypovitaminosis D: Case Report and Review of the Literature - Kirsten C. Webb; Magdalena Harasimowicz; Monica Janeczek; Jodi Speiser; James Swan; Rebecca Tung (Hindawi Limited, 2017)
Dasatinib is a second-generation tyrosine kinase inhibitor (TKI) used to treat imatinib-resistant chronic myelogenous leukemia (CML), as well as other Philadelphia chromosome-positive lymphoproliferative disorders. While the most commonly reported cutaneous side effects with this therapy include a morbilliform eruption, skin exfoliation, and skin irritation, pigmentary abnormalities have also been observed, albeit much more rarely. We present the case of a 72-year-old South Asian male with CML who presented with new-onset hypopigmentation of his face and scalp three years after a dose increase of dasatinib therapy, in the setting of newly discovered borderline hypovitaminosis D. Dasatinib and the other TKIs are believed to induce dyschromias via modulation of the c-kit receptor and its associated signaling pathway, which is involved in melanocyte survival, proliferation, and migration.